IDNLearn.com: Your go-to resource for finding precise and accurate answers. Ask your questions and receive reliable, detailed answers from our dedicated community of experts.
Sagot :
To solve the equation [tex]\( x^2 + 4x = 1 \)[/tex] by completing the square, follow these steps:
1. Rewrite the equation in standard form:
[tex]\[ x^2 + 4x - 1 = 0 \][/tex]
2. Move the constant term to the other side of the equation:
[tex]\[ x^2 + 4x = 1 \][/tex]
3. Complete the square:
To complete the square, add and subtract the square of half the coefficient of [tex]\( x \)[/tex] within the equation. The coefficient of [tex]\( x \)[/tex] is 4, so half of this coefficient is 2 and its square is [tex]\( 2^2 = 4 \)[/tex].
[tex]\[ x^2 + 4x + 4 - 4 = 1 \][/tex]
This can be written as:
[tex]\[ (x + 2)^2 - 4 = 1 \][/tex]
4. Isolate the perfect square term:
[tex]\[ (x + 2)^2 = 1 + 4 \][/tex]
[tex]\[ (x + 2)^2 = 5 \][/tex]
5. Take the square root of both sides:
[tex]\[ x + 2 = \pm \sqrt{5} \][/tex]
6. Solve for [tex]\( x \)[/tex]:
[tex]\[ x = -2 \pm \sqrt{5} \][/tex]
Hence, the solutions are:
[tex]\[ x = -2 + \sqrt{5} \][/tex]
[tex]\[ x = -2 - \sqrt{5} \][/tex]
Given the options, the correct choice is:
[tex]\[ x = \pm \sqrt{5} - 2 \][/tex]
1. Rewrite the equation in standard form:
[tex]\[ x^2 + 4x - 1 = 0 \][/tex]
2. Move the constant term to the other side of the equation:
[tex]\[ x^2 + 4x = 1 \][/tex]
3. Complete the square:
To complete the square, add and subtract the square of half the coefficient of [tex]\( x \)[/tex] within the equation. The coefficient of [tex]\( x \)[/tex] is 4, so half of this coefficient is 2 and its square is [tex]\( 2^2 = 4 \)[/tex].
[tex]\[ x^2 + 4x + 4 - 4 = 1 \][/tex]
This can be written as:
[tex]\[ (x + 2)^2 - 4 = 1 \][/tex]
4. Isolate the perfect square term:
[tex]\[ (x + 2)^2 = 1 + 4 \][/tex]
[tex]\[ (x + 2)^2 = 5 \][/tex]
5. Take the square root of both sides:
[tex]\[ x + 2 = \pm \sqrt{5} \][/tex]
6. Solve for [tex]\( x \)[/tex]:
[tex]\[ x = -2 \pm \sqrt{5} \][/tex]
Hence, the solutions are:
[tex]\[ x = -2 + \sqrt{5} \][/tex]
[tex]\[ x = -2 - \sqrt{5} \][/tex]
Given the options, the correct choice is:
[tex]\[ x = \pm \sqrt{5} - 2 \][/tex]
Your participation means a lot to us. Keep sharing information and solutions. This community grows thanks to the amazing contributions from members like you. Your search for answers ends at IDNLearn.com. Thank you for visiting, and we hope to assist you again soon.